Views on and experiences of electronic cigarettes: a qualitative study of women who are pregnant or have recently given birth. - Bowker, Katharine; Orton, Sophie; Cooper, Sue; Naughton, Felix; Whitemore, Rachel; Lewis, Sarah; Bauld, Linda; Sinclair, Lesley; Coleman, Tim; Dickinson, Anne; Ussher, Michael (BioMed Central, 2018)
Background: Electronic cigarettes (ECs) are increasingly used for reducing or stopping smoking, with some studies showing positive outcomes. However, little is known about views on ECs during pregnancy or postpartum and previous studies have nearly all been conducted in the US and have methodological limitations, such as not distinguishing between smokers and ex/non-smokers. A greater understanding of this topic will help to inform both clinicians and EC interventions. We elicited views and experiences of ECs among UK pregnant or recently pregnant women. Methods: We conducted semi-structured telephone interviews, using topic guides, with pregnant or recently pregnant women, who were current or recent ex-smokers. To ensure broad views of ECs were obtained, recruitment was from several geographical locations and via various avenues of recruitment. This included stop smoking services, antenatal and health visitor clinics, a pregnancy website and an informal network. Participants were 15 pregnant and 15 postpartum women, including nine current EC users, 11 ex-users, and 10 never-users. Five women who were interviewed in pregnancy were later interviewed in postpartum to explore if their views had changed. Audio data was transcribed verbatim and framework analysis was applied. Results: Five main themes emerged: motivations for use (e.g., for stopping or reducing smoking), social stigma (e.g., avoiding use in public, preferring ‘discrete’ NRT), using the EC (e.g., mostly used at home); consumer aspects (e.g., limited advice available), and harm perceptions (e.g., viewed as less harmful than smoking; concerns about safety and addiction). Conclusions: ECs were viewed positively by some pregnant and postpartum women and seen as less harmful than smoking and useful as aids for reducing and stopping smoking. However, due to perceived social stigma, some women feel uncomfortable using ECs in public, especially during pregnancy, and had concerns about safety and nicotine dependence. Health professionals and designers of EC interventions need to provide women with up-to-date and consistent information and advice about safety and dependence, as well as considering the influence of social stigma.